2003
DOI: 10.1128/aac.47.4.1427-1429.2003
|View full text |Cite
|
Sign up to set email alerts
|

Integron-Associated Antibiotic Resistance in Salmonella enterica Serovar Typhi from Asia

Abstract: Eighteen of 25 isolates of Salmonella enterica serovar Typhi were multidrug resistant and contained class 1 integrons with a single cassette, dfrVII or aadA1. The dfrVII-containing integron was likely borne on an IncHI1 plasmid. Salmonella serovar Typhi could become resistant to broad-spectrum cephalosporins by integrating cassettes, such as veb-1, a common cassette in Asia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 24 publications
5
29
0
4
Order By: Relevance
“…In this study, all MDR S. Typhi strains harbored a class 1 integron carrying the dfrA7 gene cassette, conferring resistance to trimethoprim, which is similar to the results of earlier studies on other S. Typhi isolates from different countries of South East Asia [8,15]. The presence of the integron must not be undervalued since two reports have already described multidrug-resistant S. Typhi strains harboring integrons with up to six drug resistance genes [34,35]. Furthermore, integrons can acquire additional resistance gene cassettes such as veb-1 or blaVIM, leading to serious problems in the management of these infections.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, all MDR S. Typhi strains harbored a class 1 integron carrying the dfrA7 gene cassette, conferring resistance to trimethoprim, which is similar to the results of earlier studies on other S. Typhi isolates from different countries of South East Asia [8,15]. The presence of the integron must not be undervalued since two reports have already described multidrug-resistant S. Typhi strains harboring integrons with up to six drug resistance genes [34,35]. Furthermore, integrons can acquire additional resistance gene cassettes such as veb-1 or blaVIM, leading to serious problems in the management of these infections.…”
Section: Discussionsupporting
confidence: 88%
“…Since the first identification in an Serratia marcescens strain isolated in Japan in 1993 and the second report associated with blaGES-1 in Klebsiella pneumoniae strain FFUL 22K, up to date, class 3 integron has only been described in Acinetobacter spp., Alcaligenes, Citrobacter freundii, Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa, Pseudomonas putida, Salmonella spp and Serratia marcescens (Arakawa et al, 1995;Correia et al, 2003;Nemergut, 2008;Segal, 1999;Naohiro Shibata, 2003;Ploy et al, 2003). Class 3 integron had been commonly reported with low incidence and mediating IMP-1 Metallo-Beta-Lactamase (Arakawa et al, 1995, Shibata, 1999.…”
Section: Class 3 Integronmentioning
confidence: 99%
“…Moreover, the dfrVII gene cassette was found in S. typhi associated with an incompatibility plasmid. 17 In this study, four stains (E5, E18, E21 and E27) isolated from poultry faeces and one stain (C15) isolated from patients were found to be positive for class I integron ( Figure 3) conferring resistance to common antibiotics such as ampicillin, cotrimoxazole, cephalexin, erythromycin, nalidixic acid and tetracycline. Stains E32, C3, C5 and C9 did not contain any plasmid and integron I but found to be different antibiotic resistance (Table 2).…”
Section: Resultsmentioning
confidence: 53%
“…The occurrence of multidrug resistance (MDR) to ampicillin, chloramphenicol, sulfonamides, streptomycin, tetracycline, and trimethoprim in Salmonella enterica serovar typhi has been increasing and MDR strains have been responsible for outbreaks on the Asian subcontinents. 17 In a multinational study in Denmark, Germany, Italy, Spain and the United States and another study in France, thus confirmed the spread and persistence of this multidrug-resistant for epidemic strain of S. enterica serotype typhimurium. 18,19 Six out of ten strains contained plasmids ranging from 140-62 MDa and the result has been shown in 20 Class I integrons are the most extensively studied integrons, which are thought to be a major factor implicated in the dissemination of antibiotic resistance.…”
Section: Resultsmentioning
confidence: 71%